WORK ETHIC OF PALM OIL WORKERS IN SUPPORTING THE FAMILY ECONOMY: A CASE STUDY AT PT. BAKRIE PASAMAN PLANTATIONS - Wulandari, Tria; M. Husen MR; Putra Rangkuty, Rakhmadsyah; Amiruddin Ketaren (FISIP Universitas Malikussaleh, 2025)
The responsibility and hard work of oil palm workers for the work they do by working as best as possible in order to get the expected results as a form of work ethic of oil palm workers in meeting the economic needs of their families. The main focus in this study is to find out the responsibility, hard work, and discipline that are the work ethic of oil palm workers and the efforts of oil palm workers in maintaining the family economy as seen from managing finances, saving, and having additional sources of income. This research was conducted at PT. Bakrie Pasaman Plantations (BPP), Koto Balingka District, West Pasaman Regency. This research uses the Motivation Theory of Abraham Maslow. The research method used is a qualitative research method with a descriptive approach that aims to describe and analyze certain phenomena in depth about what the research subject experienced. The results of this study show that the work ethic of oil palm workers can be seen from the sense of responsibility, hard work, and discipline towards the work they do by doing the work in a directed manner to get optimal results. Then the efforts made by oil palm workers in maintaining their family's economy are by working side jobs such as working on privately owned plantations and opening stall businesses such as basic necessities, coffee shops, fried foods, and lontong stalls.